Sea Level Projections From IPCC Special Report on the Ocean and Cryosphere Call for a New Climate Adaptation Strategy in the Skagerrak-Kattegat Seas - Su, Jian; Andrée, Elin; Nielsen, Jacob W.; Olsen, Steffen M.; Madsen, Kristine S. (Frontiers in Marine Science, 2021)
Denmark has a long, complex coastline, connecting the North Sea in the west to the semi-enclosed Baltic Sea in the east, via the Skagerrak-Kattegat Seas. Historical sea level records indicate that relative sea level (RSL) has been increasing along the Danish North Sea coast, south of Skagerrak, following the global mean sea level (GMSL) rise. In the central Skagerrak-Kattegat Seas, RSL rise has been practically absent, due to the GMSL rise being off-set by the Fennoscandian post-glacial land-uplift. The new IPCC Special Report on the Ocean and Cryosphere in a Changing Climate (SROCC) reported that under RCP8.5 GMSL will increase more than the previous estimates in the IPCC Fifth Assessment Report (AR5) at the end of twenty-first century due to Antarctic ice sheet dynamics. We performed a regionalization of the SROCC sea level projections for the “Danish Climate Atlas” dataset, a nation-wide climate adaptation dataset based on IPCC and various national and international databases. In these complementary datasets, important local data have been considered, which have not been included in the IPCC SROCC GMSL rise estimates, i.e., more precise national-wide land-rise prediction and sets of sea level fingerprints. Our results indicate that sea level projections under RCP8.5 results in a > 40 cm RSL rise at the end of the twenty-first century in the Skagerrak-Kattegat Seas, which might call for a new adaptation strategy in this region. The rate of mean sea level rise will exceed the rate of the land-rise earlier than the previous estimates by AR5 under the RCP8.5 scenario. In particular, we stress how these new estimates will affect future extreme sea levels in this region. Based on our results, we suggest this more recent GMSL projection needs to be considered in coastal risk assessments in the Skagerrak-Kattegat Seas also in this century.